The relationship between magnesium deficiency and depression, and the effects of magnesium supplementation on depression symptoms – literature review - Białas, Filip; Płaczek, Alicja; Machaj, Dominik; Baciur, Patrycja; Skowrońska, Katarzyna (Journal of Education, Health and Sport, 2022)
Magnesium is a very important macronutrient in the human body. Its main storage is bones. The correct concentration of this macronutrient within the normal range is necessary for the proper functioning of the body. Deficiency of this element negatively affects the entire body. One of the symptoms of magnesium deficiency is depression and other psychiatric disorders. The factors explaining the mechanism of magnesium's antidepressant effect are not fully understood, however, a relationship between magnesium deficiency and the pathogenesis of depression has been demonstrated. Supplementation with preparations of this element improves the condition in ill people with depression. [3][6]